If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying SD = (4Y + 5) Reorder the terms: DS = (5 + 4Y) Remove parenthesis around (5 + 4Y) DS = 5 + 4Y Solving DS = 5 + 4Y Solving for variable 'D'. Move all terms containing D to the left, all other terms to the right. Divide each side by 'S'. D = 5S-1 + 4S-1Y Simplifying D = 5S-1 + 4S-1Y
| 6(x-4)-3(x-2)=9 | | 89=5w+9 | | 2x^3+x-100=0 | | 200+11x= | | y=8ex | | 54=3v+12 | | 4w+13=45 | | (4x-11)=2 | | Y-10=13 | | 8t-60+15t=-2x-5t | | 3w+16=76 | | 8+1+2t=4t+12 | | 8+1-2t=4t-12 | | 8+1-2t=4t+12 | | 8cos^4x+1=0 | | (6x^2*y^2)*(-3x^4*y^3*z^3)= | | 3y-6x=-17 | | X^5+6x^4+4x^3-24x^2-16x+32=0 | | -3y+5=2y-10 | | -3y+5=2y-1o | | 5+15x=100 | | 4x+-6x-2=-1 | | 2y+3=6-y | | 9y-(4y+y)=24 | | 7(x+2)=2(2a-1) | | int(cosX)dx= | | 3w^3-5w^2-27w+45=0 | | 14=c^2+5c | | 3w^2-5w^2-27w+45=0 | | (-20x^2)+19x+2=0 | | y+3x=360 | | (-6hi^3j^4)(6h^2i^0j^3)=0 |